Tanggung Jawab Hukum Badan Pertanahan Nasional dalam Kasus Pemagaran Laut Tangerang oleh Korporasi - Siti Iin; Sumarmi Pujiestu; Dina Atika Oktafiana; Yudi Widagdo Harimurti (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
The Tangerang sea fencing has become a polemic because it violates Article 33 paragraph (3) of the Constitution, which states that the land, air, and natural resources contained therein may not be controlled by individuals or corporations. Because natural resources belong to the state. This issue highlights indications of control of natural resources by corporations that cause losses to coastal communities. This study aims to examine the legal responsibility of the National Land Agency (BPN) in the sea fencing case and to assess the administrative and land law aspects that are violated. The research method used is normative juridical research with a regulatory approach and case studies, supported by analysis of official documents, legal literature, and related court decisions. The results of the study indicate that the BPN has legal responsibility in the form of supervision and control over the granting of land rights that have implications for control of coastal areas. In addition, the BPN also ensures that land management rights do not conflict with the principles of social justice and the right to access natural resources. The discussion of the research emphasizes the need for an active role of the BPN in preventing the practice of privatization of marine and coastal land spaces by corporations that are detrimental to the public interest, as well as strengthening the monitoring and transparency system in granting permits.